Pengaruh Gaya Belajar Terhadap Hasil Belajar Mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Medan: Studi Pendahuluan - Leni Rahma Dani; Sekar Arumi Kinasih; Dwi Wulandari; Azzahra Dwina; Fanni Joice Putri Sitohang; Retta Uli Sitohang (CV. Eracita Grup, 2026)
Learning outcomes are an important indicator of the success of learning in higher education and are influenced by various internal factors, one of which is learning style. This preliminary study aims to identify students’ learning style tendencies and analyze the effect of learning styles on the perceived learning outcomes of students at the Faculty of Education, Universitas Negeri Medan. This research employed a quantitative approach with a descriptive research design. As a pilot study, the subjects consisted of 29 students from several study programs within the Faculty. Data were collected using a closed-ended Likert scale questionnaire to measure visual, auditory, and kinesthetic learning styles, as well as self-reported learning outcomes. Data analysis was conducted using descriptive statistics and regression analysis. The results showed a dominant tendency toward visual learning styles. The model test indicated a positive relationship with moderate strength (R = 0.576), contributing 33.2% to learning outcomes. Partially, only the visual learning style had a significant effect on students’ learning outcomes (p < 0.05). This study concludes that visual learning styles play an important role in improving students’ outcomes. Therefore, lecturers are encouraged to develop adaptive visual-based learning strategies.